Improving the investigation of suspected deep vein thrombosis in the Emergency Department. Issue 2 (22nd November 2013) - Daum, Peter
Abstract: Deep vein thrombosis is an important medical condition that requires treatment to prevent further complications. However, diagnosing deep vein thrombosis is not straightforward because its symptoms can mimic a number of alternative diagnoses - often leading to unnecessary investigation. The latest NICE guidance published in June 2012 provides a clear evidence-based approach to diagnosis which helps to minimise this potential loss of valuable time and resources. It was recognised that the Emergency Department was unaware of the latest guidance and demonstrated that it was often over and inadequately investigating suspected deep vein thromboses, unnecessarily using resources and putting patients at risk. To address this, a new investigation pathway and proforma were introduced into the department. It was placed onto the Trust website and incorporated into the departmental induction for new staff and trainees. Following the introduction of these changes, a re-audit demonstrated that the department's investigation of deep vein thrombosis improved significantly. In addition to increased adherence to the latest guidelines and improved documentation there was a 21% reduction in the total number of ultrasound scans performed indicating a significant impact upon both the department and patient care.